Portuguese language as instrument of reception in Lomba do Pinheiro: reports of pedagogical practices - Andrighetti, Graziela Hoerbe; Perna, Cristina Becker Lopes; Porto, Martha Machado (BELT - Brazilian English Language Teaching Journal, 2017)
The current international migratory flows bring a new reality to many Brazilian cities and point to the need for actions that allow the integration of the migratory population in our society. Understanding the offer of courses aimed at teaching the Portuguese language as an instrument of reception policy for immigrants and refugees, and aware of the demands for specific didactic materials aimed at teaching Portuguese as an Additional Language (hereinafter PAL) that meet this new reality in Brazil, we share in this article our classroom experiences with the teaching of Portuguese to a group of 30 Haitians, seeking to contribute to reflections about the teaching of Portuguese in this specific context. To do so, we describe the decisions taken along the course regarding the classes and didactic materials used, taking into account the profile of the students and the context in which they were inserted. Based on our reports, we hope to collaborate with teachers who are involved in the teaching of Portuguese for Immigrants and Refugeesin Brazilian contexts in which the migratory flow is a reality.